A Post‐Synthetically Modified MOF for Selective and Sensitive Aqueous‐Phase Detection of Highly Toxic Cyanide Ions. Issue 3 (10th December 2015) - Karmakar, Avishek; Kumar, Naveen; Samanta, Partha; Desai, Aamod V.; Ghosh, Sujit K.
Abstract: Selective and sensitive detection of toxic cyanide (CN − ) by a post‐synthetically altered metal–organic framework (MOF) has been achieved. A post‐synthetic modification was employed in the MOF to incorporate the specific recognition site with the CN − ion over all other anions, such as Cl −, Br −, and SCN − . The aqueous‐phase sensing and very low detection limit, the essential prerequisites for an effective sensory material, have been fulfilled by the MOF. Moreover, the present detection level meets the standard set by the World Health Organization (WHO) for the permissible limit of cyanide concentration in drinking water. The utilization of MOF‐based materials as the fluorometric probes for selective and sensitive detection of CN − ions has not been explored till now. Abstract : Going hunting ! Selective and sensitive detection of toxic cyanide (CN − ) by a post‐synthetically altered metal–organic framework (MOF) has been achieved (see scheme). The aqueous‐phase sensing and very low detection limit, the essential prerequisites for an effective sensory material, has been fulfilled by the MOF. Moreover, the present detection level meets the standard set by the World Health Organization (WHO) for the permissible limit of cyanide concentration in drinking water.